THE NATIONALIZATION OF PRIMARY EDUCATION IN LIMÓN, COSTA RICA, AS AN EDUCATION POLICY FOR THE NATIONALIZATION OF THE AFRO-CARIBBEAN POPULATION (1915-1950) - Hurtado Madrigal, Robert (2024)
This research delves into the social perceptions expressed by different actors regarding the ideological and political problematization surrounding private schools (Afro-Caribbean, English schools, or private schools) in the province of Limón, Costa Rica, during 1915-1950. Firstly, it explains how elements of Costa Rican national identity (language, culture, history, etc.) in the pedagogy and curriculum of these educational institutions became a matter of concern for the nationalization of Afro-Caribbean children as Costa Ricans. Secondly, it provides a detailed account of the institutional response driven by the State in different contexts for the nationalization of education and its relationship with local socio-educational actors, as part of the nationalization project for the Afro-Caribbean population through instruction. Finally, it briefly explains the contradiction in the nationalizing discourse of seeking to incorporate this population as Costa Ricans and have them adopt national identity through public instruction, while simultaneously denying rights to this population from the State.